Gestion des écosystèmes forestiers denses d’Afrique tropicale humide: references bibliographique Cameroun, Centrafrique, Congo, Côte d’Ivoire et Gabon - Dupuy, B.; Nasi, Robert (1999)
This bibliography for the Republic of Congo is a sequel to the one on Gabon. It comprises 312 annotated references on thematic areas: fauna, flora, vegetation, ecology, conservation, silviculture, forest inventory, forest management, forest policy and economy, non-timber forest products, etc.; and a 20-page presentation of the country and its forests This was produced by a joint CIFOR/CIRAD-Forêt FORAFRI project.